The impact of a targeted Arab Board of Emergency Medicine examination preparation course on resident success rates - Shahzad Anjum; Khalid Bashir; Haris Iftikhar; Biju Gafoor; Aftab Mohammad Umar (International Journal of Emergency Medicine)
Abstract Background The Arab Board of Emergency Medicine (ABEM) examination is a critical milestone for emergency medicine residents (EMRs) aiming to transition to independent practice. Prior to this study, no structured course had been administered to prepare EMRs for the ABEM examination. To address this gap, a five-day evening preparatory course was developed, designed to align with ABEM requirements and deliver updated, essential knowledge. This study aims to evaluate the impact of this newly introduced preparatory course on EMRs’ success rates on the ABEM examination from 2017 to 2021. Methods The five-day in-person course was conducted annually in the evenings to accommodate both EMRs and faculty, scheduled approximately six weeks before the ABEM examination. The course content was specifically aligned with ABEM standards, focusing on relevant and contemporary knowledge. EMRs participated in assessments modeled after the ABEM examination, using standardized rubrics. Pass rates were compared to historical data, and demographic variables were thoroughly analyzed. Feedback was collected from both EMRs and faculty after each course to continuously refine and improve course content and delivery. Results Data were collected over a five-year period (2017–2021), with 49 emergency medicine residents (EMRs) (100%) participating in the course. The majority of participants were male (69.4%), and the cohort included graduates from diverse regions, including Sudan (22.4%) and Pakistan (18.4%). The overall pass rate for the Arab Board of Emergency Medicine (ABEM) examination significantly increased to 91.8%, compared to a pre-course pass rate of 60%. No significant impact on outcomes was observed based on factors such as gender, country of graduation, year of participation, or initial confidence levels. Feedback from both participants and faculty indicated high levels of satisfaction with the course, with recommendations for further content refinement and the inclusion of additional Objective Structured Clinical Examination (OSCE) stations. Conclusion The findings demonstrate the significant impact of the newly introduced, face-to-face, five-day ABEM preparatory course on EMR pass rates, potentially serving as a model for similar programs in other specialties. The results highlight the importance of targeted, up-to-date instruction in improving the confidence and success of EMRs on the ABEM examination. Furthermore, the course’s development and the incorporation of ongoing feedback played key roles in further enhancing the quality and effectiveness of the training program.